Current treatment methods to improve the bioactivity and bonding strength of PEEK for dental application: A systematic review. (19th January 2023) - Ma, Tongtong; Zhang, Jiajia; Sun, Shuoyao; Meng, Wenqing; Zhang, Yan; Wu, Junling
Graphical abstract: Abstract: Polyetheretherketone (PEEK) is increasingly popular for use in dental applications because of its excellent chemical stability, biocompatibility, and mechanical qualities. However, its surface inertness hinders the osseointegration of the implant and limits the bonding strength of prostheses, significantly limiting its clinical application overall. During recent decades, there has been more and more attention to improve surface inertness of PEEK via various modification methods. Here, our work is aimed to review and discuss recent progress on the application of treatment strategies proposed to enhance the bonding strength and bioactivity of PEEK materials, including surface modification and blending modification. Surface modification was divided into physical modification, chemical modification and surface coating, according to the surface treatment approaches. Despite the challenges, modified PEEK, in our perspective, will be a viable material for dental applications.